Computational Earthquake Physics: Simulations, Analysis and Infrastructure, Part I - Yin, Xiang-chu.; Yin, Xiang-chu.; Mora, Peter.; Mora, Peter.; Donnellan, Andrea.; Donnellan, Andrea.; Matsu'ura, Mitsuhiro.; Matsu'ura, Mitsuhiro. (Pageoph Topical Volumes, 2006)
Exciting developments in earthquake science have benefited from new observations, improved computational technologies, and improved modeling capabilities. Designing realistic supercomputer simulation models for the complete earthquake generation process is a grand scientific challenge due to the complexity of phenomena and range of scales involved from microscopic to global. The book is divided into two parts: The present volume - Part I - focuses on microscopic simulation, scaling physics, dynamic rapture and wave propagation, earthquake generation, cycle and seismic pattern. Topics covered range from numerical developments, rupture and gouge studies of the particle model, Liquefied Cracks and Rayleigh Wave Physics, studies of catastrophic failure and critical sensitivity, numerical and theoretical studies of crack propagation, developments in finite difference methods for modeling faults, long time scale simulation of interacting fault systems, modeling of crustal deformation, through to mantle convection.